Logic Pro 9 - Cousins, Mark; Hepworth-Sawyer, Russ (Routledge, 2012)
First published in 2010. Routledge is an imprint of Taylor & Francis, an informa company.
Online resource; Title from title page (viewed August 21, 2012)
Keywords: Web publishing; Interactive multimedia; Music -- Computer network resources; Édition sur le Web; Multimédias interactifs; Music; Computer network resources